The translation unit from the textual and cognitive perspective - Menin, Roberto (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
The abandonment of linguistic theories relating to the concept of equivalence has left us with a void, namely how to adequately identify the translation unit itself. Previously, this has been defined either lexically (word, lexeme, collocation, etc.) or syntactically (syntagma, etc.) and the maximal level was fixed within the sentence. Linguistic theories have also described the relationship between original text and translation in terms of equivalence. Today, textual linguistics, pragmatics and cognitivist theories have placed the text, in its entirety, in relation to other texts and communication phenomena, at the very centre of analysis. But the microtextual level still exists, and translators proceed to translate from individual units, not from the overall text. The author of the article explains how it is possible to identify the translation unit in a textual and cognitive sense, and to understand what happens in the process of interlinguistic and intercultural change.